Doctorates Conferred in the Sciences by American Universities 1931-1932: Reprint and Circular Series of the National Research Council (The National Academies Press, 1932)
Keywords: Math, Chemistry, and Physics

Why Indoor Chemistry Matters - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
People spend the vast majority of their time inside their homes and other indoor environments where they are exposed to a wide range of chemicals from building materials, furnishings, occupants, cooking, consumer products, and other sources. Despite research to date, very little is known about how exposures to indoor chemicals across complex chemical phases and pathways affect human health. The COVID-19 pandemic has only increased public awareness of indoor environments and shed light on the many outstanding questions about how best to manage chemicals indoors. This report identifies gaps in current research and understanding of indoor chemistry and new approaches that can be applied to measure, manage, and limit chemical exposures. Why Indoor Chemistry Matters calls for further research about the chemical transformations that can occur indoors, pathways and timing of indoor chemical exposure, and the cumulative and long-term impacts of exposure on human health. Research priorities should consider factors that contribute to measurable environmental health disparities that affect vulnerable populations, such as the age, location, and condition of buildings that can alter exposures to indoor chemicals.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies